Subcutaneous Implantable Cardioverter Defibrillator: A Contemporary Overview - Fabrizio Guarracini; Alberto Preda; Eleonora Bonvicini; Alessio Coser; Marta Martin; Silvia Quintarelli; Lorenzo Gigli; Matteo Baroni; Sara Vargiu; Marisa Varrenti; Giovanni Battista Forleo; Patrizio Mazzone; et al. (Life, 2023)
The difference between subcutaneous implantable cardioverter defibrillators (S-ICDs) and transvenous ICDs (TV-ICDs) concerns a whole extra thoracic implantation, including a defibrillator coil and pulse generator, without endovascular components. The improved safety profile has allowed the S-ICD to be rapidly taken up, especially among younger patients. Reports of its role in different cardiac diseases at high risk of SCD such as hypertrophic and arrhythmic cardiomyopathies, as well as channelopathies, is increasing. S-ICDs show comparable efficacy, reliability, and safety outcomes compared to TV-ICD. However, some technical issues (i.e., the inability to perform anti-bradycardia pacing) strongly limit the employment of S-ICDs. Therefore, it still remains only an alternative to the traditional ICD thus far. This review aims to provide a contemporary overview of the role of S-ICDs compared to TV-ICDs in clinical practice, including technical aspects regarding device manufacture and implantation techniques. Newer outlooks and future perspectives of S-ICDs are also brought up to date.